2022
DOI: 10.1021/acs.analchem.2c02025
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Channel Recognition of Human Serum Albumin and Glutathione by Fluorescent Probes with Site-Dependent Responsive Features

Abstract: Design of chemical probes with high specificity and responses are particularly intriguing. In this work, a fluorescent probe (M–OH–SO 3 ) with dual-channel spectral responses toward human serum albumin (HSA) is presented. By employing dinitrobenzenesulfonate as a recognition site as well as a fluorescence quencher, probe M–OH–SO 3 displayed weak fluorescence, which, nevertheless, exhibits extensive yellow (575 nm) and red (660 nm) fluorescence emissions toward HSA under excitations at 400 and 500 nm, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The ability of HSA to promote various chemical transformations is related to the existence of two highly reactive residues Lys199 and Tyr411, which are strategically located at two sites (site I and site II) . To clarify the mechanism of HSA-catalyzed 1 hydrolysis, the catalytic sites were first explored by adding site-specific inhibitors (warfarin for site I and ibuprofen for site II , ) into HSA. As shown in Figures A,B and S14, as the concentration of warfarin or ibuprofen increases (0 to 60-fold higher than the concentration of 1 ), the capability of HSA to promote 1 hydrolysis is gradually suppressed, indicating that both sites play a role in the catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of HSA to promote various chemical transformations is related to the existence of two highly reactive residues Lys199 and Tyr411, which are strategically located at two sites (site I and site II) . To clarify the mechanism of HSA-catalyzed 1 hydrolysis, the catalytic sites were first explored by adding site-specific inhibitors (warfarin for site I and ibuprofen for site II , ) into HSA. As shown in Figures A,B and S14, as the concentration of warfarin or ibuprofen increases (0 to 60-fold higher than the concentration of 1 ), the capability of HSA to promote 1 hydrolysis is gradually suppressed, indicating that both sites play a role in the catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Human serum albumin (HSA) is a biocompatible protein carrier suitable as a host for enhancing the imaging capacity of small-molecule probes, and as such a number of fluorescent dyes with HSA binding capacity have been developed. [35][36][37][38] Besides ONOO − sensing, we have demonstrated the applicability of HSA encapsulation for the enhanced fluorescence imaging of lysosomes based on receptor-directed endocytosis, 25 and intracellular glycosidases using super-resolution microscopy. 27 In addition, we have shown that this strategy could be extended to targeted fluorescence imaging of triple-negative breast cancer in vivo.…”
Section: Papermentioning
confidence: 99%
“…In order to obtain novel NIR fluorescent probes that are structurally simple and can be facilely synthesised, we abandon the coumarin moiety and resorted to the dicyanoisophorone fluorophore because its derivatives constitute a reservoir of NIR sensors with simple structures by straightforward modification of dicyanoisophorone. [56][57][58][59][60][61][62][63] In this article we envisage to design and synthesise a fluorescently activated NIR probe for the detection of Ag + /Hg 2+ based on intramolecular charge transfer (ICT) effect, by condensation of 4-diethylamino salicylaldehyde with dicyanoisophorone and subsequent esterification with phenyl chlorothionocarbonate. Dicyanoisophorone as a strong electron-withdrawing group and diethylamino as an electron donor were introduced into the NIR fluorescent probe (N-FP) to achieve large Stokes shift, strong luminescence and ICT effect, and the emission wavelength in NIR region.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the chemosensor based on coumarin‐dicyanoisophorone dyad suffers from multistep synthesis. In order to obtain novel NIR fluorescent probes that are structurally simple and can be facilely synthesised, we abandon the coumarin moiety and resorted to the dicyanoisophorone fluorophore because its derivatives constitute a reservoir of NIR sensors with simple structures by straightforward modification of dicyanoisophorone 56–63 . In this article we envisage to design and synthesise a fluorescently activated NIR probe for the detection of Ag + /Hg 2+ based on intramolecular charge transfer (ICT) effect, by condensation of 4‐diethylamino salicylaldehyde with dicyanoisophorone and subsequent esterification with phenyl chlorothionocarbonate.…”
Section: Introductionmentioning
confidence: 99%